THE ROLE OF DIGITAL MARKETING IN BOOSTING MSME MARKETING PERFORMANCE - Nofrisel Nofrisel; Edhie Budi Setiawan; Dian Artanti Arubusman; Theresye Yoanyta Octora; Amrulloh Ibnu Kholdun (Pusat Riset dan Inovasi Nasional, 2023)
Finding out how digital marketing affects the marketing effectiveness of micro, small, and medium-sized firms (MSMEs) in East Java, Indonesia, is the aim of this study. Data from 351 SMEs were gathered using the structural equation model (SEM) to evaluate the research hypothesis. According to the study's results, digital marketing considerably improves MSMEs' marketing efficiency. It was also discovered that digital marketing acts as a link between the marketing performance and capabilities of MSMEs. For MSMEs in East Java and other parts of Indonesia, as well as for policymakers and academics interested in promoting the growth and development of the MSME sector, these findings have significant ramifications.